Establishing Normative Data for Pupillometer Assessment in Neuroscience Intensive Care: The "END-PANIC" Registry. Issue 4 (August 2017) - Olson, DaiWai M.; Stutzman, Sonja E.; Atem, Folefac; Kincaide, Julia D.; Ho, Thuy-Tien; Carlisle, Byron A.; Aiyagari, Venkatesh
Abstract : ABSTRACT: Background: Trained medical practitioners have been assessing the pupillary light reflex for more than 2 millennia. However, the interrater reliability of the pupillary light reflex remains low. To overcome the drawbacks of a subjective interpretation of pupillary size and reactivity, automated pupillometers are becoming increasingly commonplace, but practitioners do not have adequate data from which to judge whether the numerical values provided by the pupillometer are "within reference limits."Methods: This article details the methods used to create an extensive database of automated pupillometer readings and associated patient data (eg, intracranial pressure).Discussion/Conclusions: The "Establishing Normative Data for Pupillometer Assessments in Neuroscience Intensive Care" Registry will provide a large data set of pupillary size, reactivity, and speed of contraction in a cohort of patients admitted to a neuroscience intensive care unit with a variety of conditions. Analysis of this data set will help establish normative data for pupillometer readings for neurologically impaired patients. Exploratory analysis of this data set may also provide preliminary hypothesis generating data for future prospective studies on pupillary findings and trends in acute neurological conditions.